2015
DOI: 10.2147/ppa.s87271
|View full text |Cite
|
Sign up to set email alerts
|

The optimal choice of medication administration route regarding intravenous, intramuscular, and subcutaneous injection

Abstract: BackgroundIntravenous (IV), intramuscular (IM), and subcutaneous (SC) are the three most frequently used injection routes in medication administration. Comparative studies of SC versus IV, IM versus IV, or IM versus SC have been sporadically conducted, and some new findings are completely different from the dosage recommendation as described in prescribing information. However, clinicians may still be ignorant of such new evidence-based findings when choosing treatment methods.MethodsA literature search was pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
81
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(84 citation statements)
references
References 91 publications
1
81
0
2
Order By: Relevance
“…The majority of injection failures was due to user error, which were rectified with additional training and slight adjustments in user instructions. It was important that patients were comfortable and confident with the device, and when choosing between an SC or IV regimen (assuming comparable efficacy and safety profiles), patient preference and pharmacoeconomics should be taken into account [21]. The availability of an alternative formulation to belimumab IV will give patients the option to self-administer at home, avoiding the need to attend the infusion clinic every month.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of injection failures was due to user error, which were rectified with additional training and slight adjustments in user instructions. It was important that patients were comfortable and confident with the device, and when choosing between an SC or IV regimen (assuming comparable efficacy and safety profiles), patient preference and pharmacoeconomics should be taken into account [21]. The availability of an alternative formulation to belimumab IV will give patients the option to self-administer at home, avoiding the need to attend the infusion clinic every month.…”
Section: Discussionmentioning
confidence: 99%
“…Thus we explored subcutaneous hAAT; by this we also achieve a slower deposition of hAAT in the serum. Interestingly, subcutaneous is preferable in a list of drugs that used to be administered intravenously/intramuscularly, including heparin and hydrocortisone (Jin et al, 2015). However here, only the 60 mg/kg group displayed prolong graft survival.…”
Section: Discussionmentioning
confidence: 99%
“…Thus it is possible that other groups failed to reach therapeutic levels early after transplantation. Considering this dose would translate to an impractical volume of subcutaneous material for human injection (Jin et al, 2015), this outcome suggests that a more concentrated formulation of clinical-grade hAAT, or a slow-release apparatus, may better emulate sustained functional levels of hAAT. The prospect of introducing hAAT subcutaneously has been tested in rabbits (Pamarthi et al, 2008) and mice (Ma et al, 2010) and is evaluated in a phase I/II trial (NCT02503683).…”
Section: Discussionmentioning
confidence: 99%
“…12,13 In addition, studies of non-antipsychotic drugs that compared formulations found patients prefer the SQ route compared to the IM route. 3,16,17,31 Spratt and colleagues found a mild or marked preference for the SQ formulation of testosterone with no patients preferring IM injections due to less pain associated with a smaller needle size. 31 Studies also found a strong preference for the SQ route of methotrexate for rheumatoid arthritis due to less pain.…”
Section: Discussionmentioning
confidence: 99%